ATTRACTION DIRECTIONS OF FOREIGN INVESTMENTS IN TERMS OF INVESTMENT ENVIRONMENT ATTRACTIVENESS (American Journal of Business Management, Economics and Banking, 2025)
The article analyzes the main directions of attracting foreign investments based on the concept of investment environment attractiveness. Investment environment attractiveness is a set of factors that determine a country’s or region’s potential to attract investors. The study examines how economic, political, legal, social, and infrastructural factors affect investment attractiveness. Additionally, it considers incentives created for foreign investors, free economic zones, tax benefits, and government support mechanisms.